Mujer Decolonial. Puesta en escena con memoria escrita (2023)
The following written memory comes after the staging of “Mujer Decolonial”, where the creative lab turns into the main methodology for the development of the staging and, at the same time, it allows me to discover new points of view to carry on with my role as a teacher and artist. I divide the process in 4 chapters, distributed as follows: 1. De la decolonilidad y otros placeres, in this chapter, I bring to the table the way I approach to the concept of decoloniality and how discovering myself as a mother, artist and teacher looking for a transformation in these roles turns me into a decolonial being.